Effect of adding acetic acid when performing magnifying endoscopy with narrow band imaging for diagnosis of Barrett’s esophageal adenocarcinoma - Ikenoyama, Yohei; Tanaka, Kyosuke; Umeda, Yuhei; Hamada, Yasuhiko; Yukimoto, Hiroki; Yamada, Reiko; Tsuboi, Junya; Nakamura, Misaki; Katsurahara, Masaki; Horiki, Noriyuki; Nakagawa, Hayato (Endoscopy International Open, 2022)
Background and study aims Magnifying endoscopy with narrow band imaging (M-NBI) was developed to diagnose Barrett’s esophageal adenocarcinoma (BEA); however, this method remains challenging for inexperienced endoscopists. We aimed to evaluate a modified M-NBI technique that included spraying acetic acid (M-AANBI).Patients and methods Eight endoscopists retrospectively examined 456 endoscopic images obtained from 28 patients with 29 endoscopically resected BEA lesions using three validation schemes: Validation 1 (260 images), wherein the diagnostic performances of M-NBI and M-AANBI were compared – the dataset included 65 images each of BEA and non-neoplastic Barrett’s esophagus (NNBE) obtained using each modality; validation 2 (112 images), wherein 56 pairs of M-NBI and M-AANBI images were prepared from the same BEA and NNBE lesions, and diagnoses derived using M-NBI alone were compared to those obtained using both M-NBI and M-AANBI; and validation 3 (84 images), wherein the ease of identifying the BEA demarcation line (DL) was scored via a visual analog scale in 28 patients using magnifying endoscopy with white-light imaging (M-WLI), M-NBI, and M-AANBI.Results For validation 1, M-AANBI was superior to M-NBI in terms of sensitivity (90.8 % vs. 64.6 %), specificity (98.5 % vs. 76.9 %), and accuracy (94.6 % vs. 70.4 %) (all P < 0.05). For validation 2, the accuracy of M-NBI alone was significantly improved when combined with M-AANBI (from 70.5 % to 89.3 %; P < 0.05). For validation 3, M-AANBI had the highest mean score for ease of DL recognition (8.75) compared to M-WLI (3.63) and M-NBI (6.25) (all P < 0.001).Conclusions Using M-AANBI might improve the accuracy of BEA diagnosis.